Manajemen Kedisiplinan Siswa di SMP Negeri 14 Surakarta - Rahayu, Endang Puji (Nur Science Institute, 2021)
This study aims to describe: 1) student discipline planning at SMP Negeri 14 Surakarta, 2) student discipline implementation at SMP Negeri 14 Surakarta, and 3) student discipline control at SMP Negeri 14 Surakarta. This type of research is a qualitative research with a case study design. Data collection techniques using the method of observation, interviews, and documentation. Data validity uses triangulation of sources and techniques. Data analysis techniques using interactive model analysis. The results of the study shows: 1) Student discipline planning is done through the identification of problems showing students are often late for school. The determination of ideas and ideas was demonstrated by the principal's meeting with all the teachers who set the innovation program